Cultural Stereotypes of Multinational Banks - Barry Eichengreen; Orkun Saka (London School of Economics and Political Science (LSE), European Institute, 2023)
Using hand-collected data spanning more than a decade on European banks' sovereign debt portfolios, we show that the trust of residents of a bank's countries of operation in the residents of a potential target country of investment has a positive, statistically significant, and economically important association with its cross-border exposures. In identifying cultural stereotypes at the bank level, we show that corporate culture at bank headquarters is influenced by foreign subsidiaries for several reasons, including banks' tendency to hire internally across borders for high-level managerial positions. We therefore leverage the geography of multinational bank branch networks to construct a bank-specific measure of culture that differs across banks headquartered in the same country, at the same point in time, with regard to the same target country. This allows us to compare how sovereign exposures are affected by cultural stereotypes while ruling out confounding factors at country and country-pair levels. The effect of stereotypes is persistent over time, stronger for less diversified banks, and weaker for target countries whose bonds appear more frequently in bank portfolios. Cultural stereotypes are particularly salient when governments are hit by sovereign debt crises.
Keywords: 330; cultural biases; stereotypes; trust; banks; sovereign debt